Pengembangan Pendidikan Soft Skill dalam Pembelajaran Statistik - Yuyun Yunarti (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2016)
Education has a central role in human life and developing era. Education is the bridge that connects the present and the future. The existence of such arole, content and process of education need to be always updated according the advancement of science and the needs of the community. The world is now moving quickly with the rate getting toned. Humans are in the midst of a revolution that is changing the style and way of life, communicate, think, and also achieve well-being. It is therefore always necessary renewal of organizing education to keep up with the rapid rate of change. One trend that demands educational anticipation is the shift in the profile of competencies that are needed in the future. Knowledge is no longer the only needs to make one successful. Soft skills, which include personal and interpersonal abilities of a person, being a basic need to master in order to be able to exist in a person’s life.